New record of blue swimming crab Callinectes sapidus Rathbun, 1896 (Crustacea: Portunidae) for the state of Rio Grande do Norte, Northeastern Brazil - Carlos Alencar; Sávio Morae; Paulo Victor Araújo; Vanessa Brito; Fúlvio Freire (Check List, 2013)
The species Callinectes sapidus is reported for the first time in the state of Rio Grande do Norte, Northeastern Brazil. In Brazil, this species is only known from the state of Rio Grande do Sul to the state of Paraíba. In this work, one more gap about the distribution of this species was discovered. Samplings were gathered in two localities: Cavalos River and Ceará-mirim River, north and east coast of Rio Grande do Norte, respectively. This new record increases information about the singular distribution of this species, known for being the only species of Callinectes with disjoint distribution in the Americas.